GAYA BELAJAR DAN MOTIVASI BELAJAR DALAM PENINGKATAN HASIL BELAJAR SISWA MENENGAH ATAS - Tafiardi Tafiardi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
There are a number of factors influenced the student’s learning achievement. Two of them are learning style and learning motivation. This article describes how the two factors affect the learning achievement and how the teacher should consider each of them in instructional process. Acknowledging the different learning styles and motivations of the students, the teachers are expected to use variety of instructional methods and media that will meet the students’ characteristics. To do this, this article presents a list if suggestions.